Ex situ conservation of tropical orchids in Ukraine - Buyun, Lyudmyla (Universidad de Costa Rica, 2015)
The problem of biodiversity conservation of tropical floras having the global ecological, economical and social importance, has already exceeded the boundaries of individual countries. Successful conservation actions require joint efforts of scientists on the local, national, regional, and international levels (Wyse Jackson & Sutherland, 2000, Grodzynsky et al., 2001).